Single-DC-Source Multilevel Inverters - Vahedi, Hani; Trabelsi, Mohamed (SpringerBriefs in Electrical and Computer Engineering, 2019)
The purpose of this book is to distinguish the single-de-source multilevel inverter topologies and to teach their control, switching and voltage balancing. It includes new information on voltage balancing and control of multilevel inverters. The book answers some important questions about the revolution of power electronics converters: 1- Why multilevel inverter are better than 2-level ones? 2- Why single-de-source multilevel inverters are a matter of interest? 3- What are the redundant switching states and what do they do? 4- How to use redundant switching states in control and voltage balancing? 5- What are the applications of single-de-source multilevel inverters?